Urea resin composition and polyurea foam
The urea resin composition forms a polyurea foam with improved flame retardancy and adhesion, addressing the limitations of urethane foams by enhancing fire resistance and durability in humid environments.
Patent Information
- Application Number
- JP2024166118
- Authority / Receiving Office
- JP · JP
- Patent Type
- Applications
- Current Assignee / Owner
- Priority Date
- 2021-03-31
- Filing Date
- 2024-09-25
- Publication Date
- 2025-01-07
- Estimated Expiration
- 2041-06-30
AI Technical Summary
Existing urethane foams used in construction and insulation applications suffer from insufficient flame retardancy, adhesion issues, and deterioration over time, especially in humid environments, leading to potential structural integrity problems during fires.
A urea resin composition is developed, comprising a polyisocyanate compound, a polyamine compound, a trimerization catalyst, a blowing agent, and a flame retardant, with minimal polyol content, forming a polyurea foam with an isocyanurate structure, which enhances flame retardancy and adhesion while resisting cracking and carbonization.
The polyurea foam exhibits excellent flame retardancy, maintains shape during combustion, suppresses deterioration in humid conditions, and ensures strong adhesion to substrates, preventing cracking and deep carbonization.
Smart Images

Figure 2025000758000022 
Figure 2025000758000001 
Figure 2025000758000002
Abstract
Description
[Technical field]
[0001] The present invention relates to a urea resin composition and a polyurea foam. [Background technology]
[0002] Urethane foam is used for construction purposes, ships for transporting oil and gas, and as a heat retaining and insulating material for electrical appliances such as refrigerators. In particular, in buildings made of reinforced concrete, the spraying method of applying urethane foam is used because it is easy to apply insulation. The spraying method is a method in which the undiluted urethane foam is sprayed onto the building frame using a spraying device, and simultaneously foamed to form a urethane foam insulation structure.
[0003] In general, polyurethane resins are characterized by excellent elasticity, flexibility, and tensile strength, as well as excellent abrasion resistance and impact strength. However, urethane foam alone is highly flammable, so studies have been conducted to improve the flame retardancy of urethane foam.
[0004] As such a urethane foam, Patent Document 1 discloses a composition for forming a water-foamed rigid polyisocyanurate foam, which comprises an organic polyphenylmethane polyisocyanate, a polyol, a trimerization catalyst, water as a blowing agent, a foam stabilizer, and a flame retardant. The invention of Patent Document 1 is characterized in that the polyol contains a chlorinated polyether polyol having a primary and / or secondary hydroxyl group, which is obtained by using an active hydrogen-containing compound as a polymerization initiator and performing ring-opening polymerization of a chlorinated epoxy compound in the presence of an acid catalyst, and that the organic polyphenylmethane polyisocyanate and the polyol are blended so that the isocyanate index is 120 to 400. It has been shown that the urethane foam using the composition for forming a water-foamed rigid polyisocyanurate foam of Patent Document 1 is excellent in the working environment and has excellent flame retardancy.
[0005] Patent Document 2 discloses a flame-retardant urethane resin composition comprising a polyisocyanate compound, a polyol compound, a trimerization catalyst, a blowing agent, a foam stabilizer and an additive, the trimerization catalyst being at least one selected from the group consisting of a nitrogen-containing aromatic compound, an alkali metal carboxylate, a tertiary ammonium salt and a quaternary ammonium salt, the additive containing red phosphorus as an essential component and at least one selected from the group consisting of a phosphoric acid ester, a phosphate-containing flame retardant, a bromine-containing flame retardant, a boron-containing flame retardant, an antimony-containing flame retardant and a metal hydroxide in combination with red phosphorus. It is shown that a urethane foam using the flame-retardant urethane resin composition of Patent Document 2 is easy to handle, has excellent flame retardancy and can form a foam that maintains a certain shape when heated. [Prior art documents] [Patent documents]
[0006] [Patent Document 1] JP 2013-023510 A [Patent Document 2] JP 2017-075326 A Summary of the Invention [Problem to be solved by the invention]
[0007] In the invention of Patent Document 1, the flame retardancy is improved by the nurate bond, but many urethane bonds are formed, and the flame retardancy may not be sufficient. In addition, the invention of Patent Document 2 describes that high flame retardancy is imparted by adding red phosphorus (powder) as a flame retardant and incorporating an isocyanurate ring, but the use of a powder flame retardant is thought to cause poor adhesion (floating) with the adherend when sprayed, for example, and there is a risk of the foam material falling off or the insulation performance decreasing due to changes over time. Patent Document 2 does not particularly mention this point. Furthermore, the inventions of Patent Documents 1 and 2 do not verify any deterioration over time due to temperature and humidity, which is important when used for construction purposes, ships for transporting oil and gas, and as insulation materials and insulation materials for electrical appliances such as refrigerators, and there is a risk of deterioration over time in a humid and hot environment. In addition, when the inventions of Patent Documents 1 and 2 are used in construction applications, for example, when exposed to flames due to fire or the like, cracks may occur or the inside of the foam may carbonize, resulting in a significant decrease in strength and possibly causing the collapse of the building.
[0008] Accordingly, an object of the present invention is to provide a urea resin composition capable of providing a novel foam different from a urethane foam, and a foam produced from the urea resin composition.
[0009] A second object of the present invention is to provide a urea resin composition capable of providing a polyurea foam having excellent flame retardancy and shape retention during combustion, capable of suppressing deterioration over time in a moist and hot environment, excellent adhesion to an adherend when applied, and which is resistant to cracking even when exposed to flame, and which is resistant to carbonization due to flame exposure progressing from the surface to its depths, and a foam thereof. [Means for solving the problem]
[0010] The present inventors have conducted intensive research to achieve the above object, and have found that a polyurea foam obtained by foaming a specific urea resin composition can solve the above problems, thereby completing the present invention.
[0011] The present invention (1) is The urea resin composition contains a polyisocyanate compound (A), a polyamine compound (B), a trimerization catalyst, a foaming agent, a foam stabilizer, and a flame retardant. The present invention (2) is This is a polyurea foam that contains a flame retardant and has an isocyanurate structure. The present invention (3) is A urea resin composition comprising a polyisocyanate compound (A), a polyamine compound (B), a trimerization catalyst, a foaming agent, and a foam stabilizer, The urea resin composition does not contain a polyol compound, or the content of the polyol compound is 1 / 5 or less in terms of mass ratio to the content of the polyamine compound (B). The present invention (4) is The composition for producing a polyurea foam contains a polyamine compound (B), a trimerization catalyst, a blowing agent, a foam stabilizer, and a flame retardant. The present invention (5) is A composition for producing a polyurea foam, comprising a polyamine compound (B), a trimerization catalyst, a blowing agent, and a foam stabilizer, The composition for producing a polyurea foam does not contain a polyol compound, or the content of the polyol compound is 1 / 5 or less, in terms of mass ratio, relative to the content of the polyamine compound (B). The present invention (6) is A urea resin composition comprising a polyisocyanate compound (A), a polyamine compound (B), a trimerization catalyst, a foaming agent, a foam stabilizer, and a flame retardant, The content of the polyamine compound (B) is 2.0% by mass or more, when the total amount of the urea resin composition is taken as 100% by mass, The content of the trimerization catalyst is 5 to 20 parts by mass relative to 100 parts by mass of the content of the polyamine compound (B) in the urea resin composition. The present invention (7) is A polyurea foam obtained by foaming and curing the urea resin composition of the invention (6). The present invention (8) is A polyurea foam having an isocyanurate structure, The polyurea foam is characterized in that the isocyanurate ratio is 25 to 50%. The isocyanurate ratio is a value calculated from the following formula (1) based on an absorption spectrum obtained by infrared spectroscopy of the polyurea foam. (Formula 1) Isocyanurate ratio (%) = P1 / (P1+P2+P3+P4) x 100 P1: Peak area derived from an isocyanurate structure contained in the absorption spectrum of a polyurea foam obtained by infrared spectroscopy P2: Peak area derived from C=O of the urea structure contained in the absorption spectrum of polyurea foam obtained by infrared spectroscopy P3: Peak area derived from C=O of urethane structure and isocyanurate structure contained in the absorption spectrum of polyurea foam obtained by infrared spectroscopy P4: Peak area derived from NH contained in the urethane structure and urea structure contained in the absorption spectrum of the polyurea foam obtained by infrared spectroscopy
[0012] The present invention may also be the following invention. The present invention (9) is This polyurea foam has an isocyanurate structure and a 5% weight loss temperature of 175°C or higher. The 5% weight loss temperature is determined by observing the weight loss behavior of the sample in a temperature range of 25 to 700°C at a heating rate of 10°C / min in a dry air stream using a differential scanning calorimeter and thermogravimetry, and measuring the temperature at which the sample loses 5% by weight. The present invention (10) is A urea resin composition comprising a polyisocyanate compound (A), a polyamine compound (B), a trimerization catalyst, a foaming agent, a foam stabilizer, and a flame retardant, The urea resin composition is characterized in that the content of the polyamine compound (B) is 2.0% by mass or more, when the total amount of the urea resin composition is taken as 100% by mass. The present invention (11) is The urea resin composition of the invention (10) is characterized in that the polyamine compound (B) has an amine value of 50 to 1000 mg KOH / g. The present invention (12) is The urea resin composition according to the invention (10) or (11) is characterized in that the polyisocyanate compound (A) has an NCO% of 10 to 35%. The present invention (13) is The urea resin composition according to any one of the above inventions (10) to (12), wherein the above polyisocyanate compound (A) is an aromatic isocyanate. The present invention (14) is The urea resin composition according to any one of the above inventions (10) to (13) is characterized in that the above flame retardant contains red phosphorus. The present invention (15) is The urea resin composition according to any one of the above inventions (10) to (14), characterized in that the flame retardant contains at least one selected from a phosphoric acid ester, a phosphate-containing flame retardant, a bromine-containing flame retardant, a boron-containing flame retardant, an antimony-containing flame retardant, and a metal hydroxide. The present invention (16) is The present invention provides a polyurea foam obtained by foaming and curing the urea resin composition according to any one of the above inventions (10) to (15). The present invention (17) is The polyurea foam is the polyurea foam of invention (16), characterized in that the total heat generated after 20 minutes is 8.5 MJ / m2 or less, as measured under heating conditions with a radiant heat intensity of 50 kW / m2 in accordance with the ISO-5660 test method. The present invention (18) is It is a polyurea foam having an isocyanurate structure. The present invention (19) is The polyurea foam of the invention (18) is characterized by containing a flame retardant. The present invention (20) is The polyurea foam according to the above invention (18) or (19), characterized in that it contains red phosphorus. The present invention (21) is In the polyurea foam of the invention (20), the content of the red phosphorus is 1 to 30 mass % relative to 100 mass % of the total mass of the polyurea foam. The present invention (22) is The polyurea foam according to any one of the above inventions (18) to (21), characterized in that the isocyanurate ratio is 10 to 50%. The isocyanurate ratio is a value calculated from the following formula (1) based on an absorption spectrum obtained by infrared spectroscopy of the polyurea foam. (Formula 1) Isocyanurate ratio (%) = P1 / (P1+P2+P3+P4) x 100 P1: Peak area derived from an isocyanurate structure contained in the absorption spectrum of a polyurea foam obtained by infrared spectroscopy P2: Peak area derived from C=O of the urea structure contained in the absorption spectrum of polyurea foam obtained by infrared spectroscopy P3: Peak area derived from C=O of urethane structure and isocyanurate structure contained in the absorption spectrum of polyurea foam obtained by infrared spectroscopy P4: Peak area derived from NH contained in the urethane structure and urea structure contained in the absorption spectrum of the polyurea foam obtained by infrared spectroscopy The present invention (23) is The polyurea foam according to any one of the above inventions (18) to (22), characterized in that it contains at least one selected from a phosphoric acid ester, a phosphate-containing flame retardant, a bromine-containing flame retardant, a boron-containing flame retardant, an antimony-containing flame retardant, and a metal hydroxide. Effect of the Invention
[0013] According to the present invention, it is possible to provide a urea resin composition capable of providing a novel foam different from a urethane foam, and a foam thereof.
[0014] Furthermore, according to the present invention, it is possible to provide a urea resin composition capable of providing a foam having sufficient flame retardancy and compressive performance, and a foam thereof.
[0015] Furthermore, according to the present invention, it is possible to provide a urea resin composition capable of providing a polyurea foam that has excellent flame retardancy and shape retention during combustion, is capable of suppressing deterioration over time in a moist and hot environment, has excellent adhesion to an adherend when applied, is resistant to cracking even when exposed to flame, and is resistant to carbonization due to flame contact that progresses from the surface to the depths, and a foam thereof. [Brief description of the drawings]
[0016] [Figure 1] FIG. 2 is an explanatory diagram illustrating a mold for molding a polyurea foam for observing the shape and average cell diameter of the cells of the present invention, and the flow direction of the foaming. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0017] 1.Urea resin composition The polyurea foam of the present invention has an isocyanurate structure. The polyurea foam can be obtained by foaming and curing a urea resin composition. The urea resin composition of the present invention is a urea resin composition containing a polyisocyanate compound (A), a polyamine compound (B), a trimerization catalyst, and a foaming agent, and preferably contains a foam stabilizer and a flame retardant. In the following description, when an upper limit value and a lower limit value are described separately, the upper limit value and the lower limit value can be freely combined to form a new numerical range.
[0018] The urea resin composition of the present invention is characterized in that the content of the polyamine compound (B) is 2.0% by mass or more, when the total amount of the urea resin composition is taken as 100% by mass.
[0019] The urea resin composition of the present invention can be foamed and cured to form a polyurea foam.
[0020] 2. Raw materials for urea resin composition 2-1. Polyisocyanate compound (A) The polyisocyanate compound (A) according to the present invention is not particularly limited as long as it does not impair the effects of the present invention. Examples of the polyisocyanate compound (A) include monomeric polyisocyanates and polymeric polyisocyanates. The monomeric polyisocyanate is a compound having a plurality of isocyanate groups at the terminals of the monomer structure. The polymeric polyisocyanate is a compound having a plurality of isocyanate groups at the terminals of the polymer structure. These polyisocyanate compounds (A) can be used alone or in combination.
[0021] Examples of the monomeric polyisocyanate include bifunctional polyisocyanate compounds such as 2,4-toluene diisocyanate (2,4-TDI), 2,6-toluene diisocyanate (2,6-TDI), m-phenylene diisocyanate, p-phenylene diisocyanate, 4,4'-diphenylmethane diisocyanate (4,4'-MDI), 2,4'-diphenylmethane diisocyanate (2,4'-MDI), 2,2'-diphenylmethane diisocyanate (2,2'-MDI), hydrogenated MDI, xylylene diisocyanate, 3,3'-dimethyl-4,4'-biphenylene diisocyanate, and 3,3'-dimethoxy-4,4'-biphenylene. Aromatic diisocyanates such as polymethylene polyphenyl polyisocyanate, 1,5-naphthalene diisocyanate, xylylene diisocyanate (XDI), hydrogenated XDI, tetramethyl xylene diisocyanate (TMXDI), etc.; alicyclic diisocyanates such as cyclohexane-1,4-diisocyanate, isophorone diisocyanate, dicyclohexylmethane-4,4'-diisocyanate, methylcyclohexane diisocyanate, etc.; alkylene diisocyanates such as butane-1,4-diisocyanate, hexamethylene diisocyanate, isopropylene diisocyanate, methylene diisocyanate, lysine diisocyanate, etc.; Examples of trifunctional or higher polyisocyanates include 1-methylbenzene-2,4,6-triisocyanate, 1,3,5-trimethylbenzene-2,4,6-triisocyanate, biphenyl-2,4,4'-triisocyanate, diphenylmethane-2,4,4'-triisocyanate, methyldiphenylmethane-4,6,4'-triisocyanate, 4,4'-dimethyldiphenylmethane-2,2',5,5'tetraisocyanate, triphenylmethane-4,4',4"-triisocyanate, polymeric MDI, lysine ester triisocyanate, 1,3,6-hexamethylene triisocyanate, 1,6,11-undecane triisocyanate, bicycloheptane triisocyanate, 1,8-diisocyanatomethyloctane, and the like. In addition, modified products and derivatives thereof may be included. Examples of modified products and derivatives thereof include isocyanurate compounds of diisocyanate compounds, adduct compounds of diisocyanate compounds, biuret compounds of diisocyanate compounds, allophanate compounds of diisocyanate compounds, and carbodiimide modified compounds of diisocyanate compounds. These polyisocyanate compounds may be used alone or in combination. Since the monomeric polyisocyanate compound forms the urea skeleton of the polyurea foam, it can be freely selected in consideration of the desired properties of the polyurea foam. Among these monomeric polyisocyanates, aromatic isocyanates are preferred in terms of excellent reactivity, MDI or modified or derivatives of MDI are more preferred, and monomeric MDI and crude MDI are even more preferred. When used as a polyurea foam for spraying, these suitable aromatic isocyanates are preferred in terms of the safety of the working environment because they have excellent reactivity. In addition, among monomeric MDI and crude MDI having the same NCO%, crude MDI containing polynuclear compounds has excellent isocyanurate ratio and therefore excellent flame retardancy.
[0022] The polymeric polyisocyanate compound includes a prepolymer obtained by reacting an excess amount of a polyisocyanate compound (C) with an active hydrogen compound having two or more active hydrogen groups, such as a polyol compound or a polyamine compound (D). The polyamine compound (D) and the polyisocyanate compound (C) are raw materials for preparing the polymeric polyisocyanate, and are not included in the polyamine compound (B) and the polyisocyanate compound (A), which are raw materials for the urea resin composition according to the present invention. Here, the polyisocyanate compound (C) may be the same as or different from the polyisocyanate compound (A).
[0023] Examples of such polyol compounds include polyester polyols and polyether polyols. Examples of polyester polyols include those obtained by condensation reaction of polyhydric alcohols and polycarboxylic acids. Examples of polyhydric alcohols include ethylene glycol, propylene glycol, butanediol, butylene glycol, glycerin, trimethylolpropane, and the like. Examples of polycarboxylic acids include glutaric acid, adipic acid, maleic acid, phthalic acid, terephthalic acid, isophthalic acid, and the like. These can be used alone or in combination. Examples of polyester polyols obtained by ring-opening condensation of caprolactone, methylvalerolactone, and the like can also be mentioned.
[0024] Examples of polyether polyols include those obtained by addition polymerization of oxides such as ethylene oxide, propylene oxide, trimethylene oxide, butylene oxide, etc., to polyhydric alcohols such as ethylene glycol, propylene glycol, diethylene glycol, glycerin, trimethylolpropane, sorbitol, etc. These can be used alone or in combination.
[0025] The polyisocyanate compound (B) to be reacted with these polyol compounds is not particularly limited as long as it does not inhibit the effects of the present invention, and examples thereof include aliphatic or aromatic polyisocyanates, mixtures thereof, and modified polyisocyanates obtained by modifying them.
[0026] The polyamine compound (D) is not particularly limited as long as it does not impair the effects of the present invention. Examples of the polyamine compound (D) include aliphatic polyamines such as triethylenetetramine, aromatic polyamines such as metaphenylenediamine, and alicyclic polyamines such as isophoronediamine. Specific examples include 4,4'-diamino-3,3'-dichlorodiphenylmethane, trimethylene-bis(4-aminobenzoate), 4,4'-diamino-3,3'-diethyl-5,5'-dimethyldiphenylmethane, polytetramethylene oxide-di-p-aminobenzoate, 2,2',6,6'-tetraethyl-4,4'-methylenedianiline, 4,4'-methylenebis(2-isopropyl-6-methylaniline), 4,4'-methylenebis(2,6-diisopropylaniline), 4,4'-methylenebis(3-chloro-2,6-diethylaniline), 3,5-diethyltoluene-2,4-diamine, and dimethylthiotoluenediamine. These may be used alone or in combination. The polyamine compound (D) may be the same as or different from the polyamine compound (B) described below.
[0027] The NCO% of the polyisocyanate compound (A) is not limited as long as it does not impair the effects of the present invention, and can be, for example, 5 to 40%, preferably 10 to 35%, and more preferably 15 to 35%. When the NCO% of the polyisocyanate compound (A) is large, a polyurea foam having high shape retention during combustion, low thermal conductivity, and capable of suppressing deterioration over time in a moist and hot environment can be obtained. That is, a polyurea foam having excellent flame retardancy and shape retention during combustion, capable of suppressing deterioration over time in a moist and hot environment, and excellent adhesion to an adherend during coating can be obtained.
[0028] The NCO% (isocyanate content) of the polyisocyanate compound (A) is measured in accordance with Method A (toluene / dibutylamine, hydrochloric acid method) of JIS K1603-1:2007 "Plastics - Polyurethane raw material aromatic isocyanate test method Part 1: Determination of isocyanate group content".
[0029] 2-2. Polyamine compounds (B) Polyamine compounds react with isocyanates to form urea bonds, which have the advantage of being water-resistant, corrosion-resistant, and resistant to chemicals such as acids and alkalis.
[0030] The polyamine compound (B) is not particularly limited as long as it does not impair the effects of the present invention. Examples of the polyamine compound (B) include aliphatic polyamines such as triethylenetetramine, aromatic polyamines such as metaphenylenediamine, and alicyclic polyamines such as isophoronediamine. Specific examples include 4,4'-diamino-3,3'-dichlorodiphenylmethane, trimethylene-bis(4-aminobenzoate), 4,4'-diamino-3,3'-diethyl-5,5'-dimethyldiphenylmethane, polytetramethylene oxide-di-p-aminobenzoate, 2,2',6,6'-tetraethyl-4,4'-methylenedianiline, 4,4'-methylenebis(2-isopropyl-6-methylaniline), 4,4'-methylene Examples of commercially available products include Iharacureamine MT, Iharacureamine M liquid, CUA-4, Curehard MED, Elasmer 250P, and Elasmer 1000P manufactured by Kumiai Chemical Industry Co., Ltd.; Lonzacure M-DEA, Lonzacure M-MIPA, Lonzacure M-DIPA, and Lonzacure M-CDEA manufactured by Lonza Japan Co., Ltd.; Ethacure 100, Ethacure 300, Ethacure 410, and Ethacure 420 manufactured by Albemarle Co., Ltd.; VERSALINK 740 manufactured by Evonik Nutrition & Care Co., Ltd.; and ANCAMINE 2049 manufactured by Evonik Co., Ltd. These may be used alone or in combination.
[0031] The amine value of the polyamine compound (B) is not particularly limited as long as it does not impair the effects of the present invention, and can be, for example, 50 to 1000 mgKOH / g, preferably 200 to 1000 mgKOH / g, more preferably 450 to 1000 mgKOH / g, and even more preferably 500 to 1000 mgKOH / g. When the amine value of the polyamine compound is within this range, a urea resin composition can be obtained that can provide a polyurea foam that has excellent flame retardancy and shape retention during combustion, can suppress deterioration over time in a moist and hot environment, has excellent adhesion to an adherend during coating, is unlikely to crack even when exposed to flame, and is unlikely to carbonize from the surface to the depth due to exposure to flame. In particular, in the total heat release test using a cone calorimeter in accordance with the ISO-5660 standard (a test that indicates flame retardancy, hereafter sometimes abbreviated as the Concalo total heat release test), the volume change rate at 600°C (a test that indicates shape retention), and the flame contact test, which will be described later, it shows excellent effects in that it forms a charred layer on the surface of the foam and can prevent fire from penetrating deep into the foam.
[0032] The amine value of the polyamine compound (B) can be measured by the method for measuring the total amine value described in JIS K1557-7:2011 "Plastics - Test methods for polyurethane raw material polyols - Part 7: Determination of basicity (indication of nitrogen content and total amine value)".
[0033] In addition to the polyamine compound (B) of the present invention, an active hydrogen compound can be added as long as it does not impair the effects of the present invention. Examples of the active hydrogen compound include alcohols such as primary alcohols, secondary alcohols, and tertiary alcohols, monools, polyol compounds, and thiol compounds. The alcohols and polyol compounds react with the polyisocyanate compound (A) to form urethane bonds and form part of the skeleton of the polyurea foam. However, since the urethane bond is more flammable than the urea bond, there is a risk that the flame retardancy of the polyurea foam may decrease. For this reason, the content of the polyol compound can be 1 / 5 or less, preferably 1 / 10 or less, by mass ratio to the content of the polyamine compound (B), and more preferably no polyol compound is included.
[0034] 2-3. Trimerization catalyst The trimerization catalyst according to the present invention is not particularly limited as long as it does not impair the effects of the present invention. By using the trimerization catalyst, an isocyanurate structure can be formed in the polyurea foam when the polyamine compound (B) is used to produce the polyurea foam. Examples of the trimerization catalyst include metal oxides such as lithium oxide, sodium oxide, and potassium oxide; Alkoxides such as sodium methoxyl, sodium ethoxyl, sodium propoxyl, sodium butoxyl, potassium methoxyl, potassium ethoxyl, potassium propoxyl, and potassium butoxyl; Organometallic salts such as potassium acetate, potassium octoate, potassium caprylate, and iron oxalate; Tertiary amines such as 2,4,6-tris(dimethylaminomethyl)phenol, N,N',N"-tris(dimethylaminopropyl)hexahydrotriazine, triethylenediamine, 1,3,5-tris(dimethylaminopropyl)hexahydro-s-triazine; derivatives of ethyleneimine; Acetylacetone chelates of alkali metals, aluminum, and transition metals; Examples include quaternary ammonium salts; diazabicycloundecene (DBU); and the like. These can be used alone or in combination. Of these, it is more preferable to use tertiary amines, organic metal salts, and diazabicycloundecene, and it is more preferable to use tertiary amines and diazabicycloundecene. By using these suitable trimerization catalysts, it is possible to obtain a polyurea foam that has excellent flame retardancy and shape retention during combustion, can suppress deterioration over time in a humid and hot environment, and has excellent adhesion to an adherend during coating.
[0035] 2-4. Foaming agent The blowing agent according to the present invention is not particularly limited as long as the effect of the present invention is not impaired. Examples of the blowing agent include water, hydrocarbons (preferably C4 to C6), hydrofluoroolefins, and carbon dioxide gas. Specific examples include cyclopentane, HFO (1336mzz), and HFO (1233zd). These can be used alone or in combination.
[0036] 2-5.Foam stabilizer The foam stabilizer according to the present invention is not particularly limited as long as the effect of the present invention is not impaired. Examples of the foam stabilizer include silicone compounds and nonionic surfactants. These can be used alone or in combination.
[0037] 2-6.Flame retardants The urea resin composition according to the present invention can contain a flame retardant. The flame retardant is not particularly limited as long as it does not impair the effects of the present invention, and examples thereof include red phosphorus, phosphoric acid ester, phosphate-containing flame retardant, bromine-containing flame retardant, boron-containing flame retardant, antimony-containing flame retardant, and metal hydroxide. These can be used alone or in combination. Among these, it is preferable to contain at least one selected from red phosphorus or a phosphate ester, a phosphate-containing flame retardant, a bromine-containing flame retardant, a boron-containing flame retardant, an antimony-containing flame retardant, and a metal hydroxide, more preferably to contain red phosphorus, and more preferably to contain at least one selected from a phosphate ester, a phosphate-containing flame retardant, a bromine-containing flame retardant, a boron-containing flame retardant, an antimony-containing flame retardant, and a metal hydroxide in addition to red phosphorus, and particularly preferably to contain red phosphorus and a phosphate ester, and further to contain at least one selected from a chlorine-containing phosphate ester, a phosphate-containing flame retardant, a bromine-containing flame retardant, a boron-containing flame retardant, an antimony-containing flame retardant, and a metal hydroxide, and particularly preferably to contain red phosphorus, a phosphate ester, and a bromine-containing flame retardant. When the urea resin composition according to the present invention contains these flame retardants, it is possible to obtain a polyurea foam having excellent flame retardancy and shape retention during combustion, capable of suppressing deterioration over time in a moist and hot environment, and excellent adhesion to an adherend during coating. Moreover, other flame retardants than these flame retardants may be contained.
[0038] The phosphoric acid ester according to the present invention is not particularly limited as long as it does not impair the effects of the present invention. Examples of the phosphoric acid ester include aromatic phosphoric acid esters such as triphenyl phosphate, cresyl diphenyl phosphate, tricresyl phosphate, trixylenyl phosphate, tris(t-butylated phenyl) phosphate, tris(i-propylated phenyl) phosphate, and 2-ethylhexyl diphenyl phosphate; Aromatic condensed phosphate esters such as 1,3-phenylene bis(diphenyl phosphate), 1,3-phenylene bis(dixylenyl) phosphate, resorcinol bis(diphenyl) phosphate, and bisphenol A bis(diphenyl phosphate); Halogen-containing phosphate esters such as tris(dichloropropyl) phosphate, tris(β-chloropropyl) phosphate, and tris(chloroethyl) phosphate; Examples of the halogen-containing condensed phosphate esters include 2,2-bis(chloromethyl)trimethylene bis(bis(2-chloroethyl)phosphate) and polyoxyalkylene bisdichloroalkyl phosphate. These can be used alone or in combination.
[0039] The phosphate-containing flame retardant according to the present invention is not particularly limited as long as it does not impair the effects of the present invention. Examples of the phosphate-containing flame retardant include monophosphates such as ammonium salts such as ammonium phosphate, ammonium dihydrogen phosphate, and diammonium hydrogen phosphate; Sodium salts such as monosodium phosphate, disodium phosphate, trisodium phosphate, monosodium phosphite, disodium phosphite, and sodium hypophosphite; Potassium salts such as monopotassium phosphate, dipotassium phosphate, tripotassium phosphate, monopotassium phosphite, dipotassium phosphite, and potassium hypophosphite; Lithium salts such as lithium monophosphate, lithium diphosphate, lithium triphosphate, lithium monophosphite, lithium diphosphite, and lithium hypophosphite; barium salts such as barium dihydrogen phosphate, barium hydrogen phosphate, barium triphosphate, and barium hypophosphite; magnesium salts such as magnesium monohydrogen phosphate, magnesium hydrogen phosphate, magnesium trimagnesium phosphate, and magnesium hypophosphite; Calcium salts such as calcium dihydrogen phosphate, calcium hydrogen phosphate, tricalcium phosphate, calcium hypophosphite; Examples include zinc salts such as zinc phosphate, zinc phosphite, and zinc hypophosphite; and aluminum salts such as aluminum monophosphate, aluminum diphosphate, aluminum triphosphate, aluminum phosphite, and aluminum hypophosphite. Examples of polyphosphates include ammonium polyphosphate, piperazine polyphosphate, melamine polyphosphate, ammonium amide polyphosphate, aluminum polyphosphate, etc. These may be used alone or in combination.
[0040] The bromine-containing flame retardant according to the present invention is not particularly limited as long as it does not impair the effects of the present invention. Examples of the bromine-containing flame retardant include pentabromodiphenyl ether, octabromodiphenyl ether, decabromodiphenyl ether, tetrabromobisphenol A (TBBA), TBBA-epoxy oligomer, TBBA-polycarbonate oligomer, TBBA-bis(dibromopropyl ether), TBBA-bis(aryl ether), and other TBBA compounds; Polybenzene ring compounds such as bisphenylpentamethane, 1,2-bis(2,4,6-tribromophenoxy)ethane, 2,4,6-tris(2,4,6-tribromophenoxy)-1,3,5-triazine, 2,6-dibromophenol, and 2,4-dibromophenol; Brominated styrene compounds such as brominated polystyrene and polybrominated styrene; Phthalic acid compounds such as ethylene bis tetrabromophthalimide; Examples of the cyclic aliphatic compounds include hexabromocyclododecane, etc.; polyacrylic acid brominated aromatic ester compounds, such as poly(pentabromophenyl acrylate); etc. These can be used alone or in combination.
[0041] The boron-containing flame retardant according to the present invention is not particularly limited as long as it does not inhibit the effects of the present invention. Examples of the boron-containing flame retardant include borax; boron oxides such as diboron trioxide, boron trioxide, diboron dioxide, tetraboron trioxide, and tetraboron pentoxide; boric acid compounds such as boric acid, lithium borate, sodium borate, potassium borate, cesium borate, magnesium borate, calcium borate, barium borate, zirconium borate, zinc borate, aluminum borate, and ammonium borate.
[0042] The antimony-containing flame retardant according to the present invention is not particularly limited as long as it does not impair the effects of the present invention. Examples of boron-containing flame retardants include antimony oxides such as antimony trioxide and antimony pentoxide; antimony salts such as sodium antimonate and potassium antimonate; pyroantimonate salts such as sodium pyroantimonate and potassium pyroantimonate; and the like. These can be used alone or in combination.
[0043] The metal hydroxide according to the present invention is not particularly limited as long as it does not impair the effects of the present invention. Examples of the metal hydroxide include aluminum hydroxide and magnesium hydroxide. These can be used alone or in combination.
[0044] As the other flame retardant, a known flame retardant can be used. As the other flame retardant, for example, chlorine compounds such as chlorinated paraffin, nitrogen compounds such as hindered amines and melamine cyanurate, cellulose, etc. can be mentioned. These can be used alone or in combination.
[0045] 2-7.Other additives In addition to the above additives, other additives may be added to the resin composition of the present invention, so long as the effects of the present invention are not impaired. Examples of other additives include resin (urea) catalysts, foaming catalysts, balance catalysts, antioxidants, ultraviolet absorbers, antibacterial agents, dispersants, and other additives that are well known in the art.
[0046] 3. Characteristics of urea resin composition The cream time of the urea resin composition according to the present invention at 5°C can be 1 to 120 seconds, preferably 2 to 70 seconds. When the cream time of the urea resin composition at 5°C is within this range, it is more effective in terms of obtaining sufficient liquid flowability and wettability and adhesion to the framework. Here, the cream time refers to the time from the time when the mixture of all the compositions of the urea resin composition except for the polyisocyanate compound (A) (hereinafter, sometimes referred to as the composition for producing a polyurea foam) is mixed with the polyisocyanate compound (A) to the time when the mixture starts to foam, becomes a creamy liquid, and starts to expand. It is measured as the time when the color of the mixture solution starts to change with the naked eye. In addition, 5°C indicates that the polyisocyanate compound (A) and the composition for producing a polyurea foam are kept at 5°C and mixed.
[0047] The cream time of the urea composition of the present invention at 20°C can be 0.5 to 90 seconds, preferably 0.7 to 60 seconds. When the cream time of the urea resin composition at 20°C is within this range, the mixed liquid thickens before the foaming agent evaporates at a practical liquid temperature, and cells do not collapse, resulting in efficient foaming, which is more effective. The cream time of the urea composition at 20°C is measured by the same measurement method as that for measuring the cream time at 5°C, except that the polyisocyanate compound (A) and the composition for producing a polyurea foam are mixed while being kept at 20°C.
[0048] 4. Characteristics of polyurea foam 4-1. Isocyanurate ratio The polyurea foam of the present invention contains an isocyanurate structure. The isocyanurate structure is formed by trimerizing the polyisocyanate compound (A), which is a raw material of the urea resin composition, with a trimerization catalyst. The isocyanurate structure can be detected by infrared spectroscopy. The proportion of the polyisocyanate compound (A) that is isocyanurated (isocyanurate ratio) is calculated by the following formula (1) based on the absorption spectrum obtained by infrared spectroscopy. The isocyanurate ratio is not particularly limited as long as it does not impair the effects of the present invention, and can be, for example, 10 to 50%, preferably 20 to 45%, and more preferably 25 to 40%. The lower limit can be 10% or more, 20% or more, 25% or more, or 28% or more, and the upper limit can be 50% or less, 45% or less, 43% or less, or 40% or less. When the isocyanurate ratio is within this range, the polyurea foam has excellent flame retardancy. (Formula 1) Isocyanurate ratio (%) = P1 / (P1+P2+P3+P4) x 100 P1: Peak area derived from an isocyanurate structure contained in the absorption spectrum of a polyurea foam obtained by infrared spectroscopy P2: Peak area derived from C=O of the urea structure contained in the absorption spectrum of polyurea foam obtained by infrared spectroscopy P3: Peak area derived from C=O of urethane structure and isocyanurate structure contained in the absorption spectrum of polyurea foam obtained by infrared spectroscopy P4: Peak area derived from NH contained in the urethane structure and urea structure contained in the absorption spectrum of the polyurea foam obtained by infrared spectroscopy
[0049] P1 is the area of the peak derived from the isocyanurate structure contained in the absorption spectrum of the polyurea foam obtained by infrared spectroscopy, and is the area of the peak derived from the isocyanurate ring at a wave number of about 1410 cm-1. P1 is the peak area in the wave number range of 1380 to 1430 cm-1. P1 indicates the content of the isocyanurate structure formed by the reaction of the isocyanate group of the raw material polyisocyanate compound (A).
[0050] P2 is the peak area derived from C=O of the urea structure contained in the absorption spectrum of the polyurea foam obtained by infrared spectroscopy, and is the area of the peak derived from C=O of the urea bond at a wave number in the vicinity of 1595 cm-1. P2 is the peak area in the wave number range of 1550 to 1640 cm-1. P2 indicates the content of the urea structure formed by the reaction of the isocyanate group of the raw material polyisocyanate compound (A).
[0051] P3 is the peak area derived from C=O of the urethane structure and isocyanurate structure contained in the absorption spectrum of the polyurea foam obtained by infrared spectroscopy, and is the peak area of the C=O bond near a wave number of 1710 cm-1. P3 is the peak area in the wave number range of 1680 to 1730 cm-1. P3 indicates the content of the urethane structure and isocyanurate structure formed by the reaction of the isocyanate group of the raw material polyisocyanate compound (A).
[0052] P4 is the peak area derived from NH contained in the urethane structure and urea structure contained in the absorption spectrum of the polyurea foam obtained by infrared spectroscopy, and is the area of the peak derived from NH near a wave number of 1510 cm-1. P4 is the peak area in the wave number range of 1470 to 1550 cm-1. P4 indicates the content of the urethane structure and urea structure contained in the polyurea foam, and indicates the content of the urethane structure and urea structure formed by reaction of the isocyanate group of the raw material polyisocyanate compound (A).
[0053] Therefore, the sum of P1 to P4 indicates the total number of isocyanate groups in the raw material polyisocyanate compound (A) that have reacted. Therefore, the isocyanurate conversion rate is a value indicating the proportion of isocyanurate structures among the isocyanate groups in the raw material polyisocyanate compound (A) that have reacted.
[0054] 4-2.Density The density of the polyurea foam is not particularly limited as long as it does not impair the effects of the present invention, but can be 10 to 200 kg / m3, preferably 10 to 100 kg / m3, and more preferably 10 to 55 kg / m3. When the density of the polyurea foam is within this range, a polyurea foam having excellent thermal conductivity and excellent flame retardancy can be obtained. The density of the polyurea foam is measured according to JIS K7222:2005 "Foamed plastics and rubber - Determination of apparent density".
[0055] 4-3. Average cell (bubble) diameter and cell shape The average cell diameter and shape of the bubbles (cells) contained in the polyurea foam are observed and measured by preparing the following test pieces and using an optical microscope (e.g., digital microscope) with a length measuring function. The test pieces are prepared by pouring a urea resin composition into a box-shaped mold (e.g., a mold for molding a foam into a rectangular parallelepiped shape), foaming and curing the composition to obtain a molded polyurea foam, and cutting out a piece of 50 mm long x 50 mm wide x 20 mm thick from the polyurea foam. Here, the test piece is taken out so that the flow direction of the foam when foamed in the mold (the direction in which the urea resin composition foams and expands, a vertical upward direction from the bottom surface of the mold. Hereinafter, this direction will be referred to as the rise direction) is the thickness direction of the test piece. The surface of the taken-out test piece with the rise direction as the normal line is the CD surface. The surface perpendicular to the CD surface of the test piece is the MD surface. The CD surface is observed with an optical microscope (including a digital microscope) to confirm its shape. In this case, 10 bubbles are randomly selected on the CD plane, and the difference (DR = R1 - R2) between the longest diameter (R1) of each bubble on the CD plane and the diameter in the direction perpendicular to that longest diameter (R2) is calculated. If the average DR of all selected bubbles exceeds 5 mm, it is determined to be an elliptical shape. Additionally, a shape between 0 mm and 5 mm is considered to be circular. In addition, ten cells in each of the CD and MD planes are randomly selected, their major axis lengths are measured, and the average is taken as the average cell diameter in the CD plane and the average cell diameter in the CD plane. The ratio of the average cell diameter in the MD plane to the average cell diameter in the CD plane (average cell diameter in the MD plane / average cell diameter in the CD plane) can be 0.7 to 1.8, and preferably 0.8 to 1.3. When these values are within the range, a polyurea foam with excellent performance can be obtained.
[0056] 4-4. Closed bubble rate The type of cells contained in the polyurea foam is not particularly limited as long as it does not impair the effects of the present invention, and may be any of closed cells, open cells, and semi-open cells. Here, the semi-open cell structure means a structure in which the cells have small pores, unlike closed cells, and in which the pores between adjacent cells are smaller than in an open cell structure. The closed cell ratio of the polyurea foam can be, for example, 75% or more, and preferably 80% or more. When the closed cell ratio is within this range, a polyurea foam with excellent performance can be obtained. The closed cell ratio is calculated by the following method. The polyurea foam is processed into a test piece of 30 mm length x 30 mm width x 20 mm thickness, and the length of each side is accurately measured to calculate the apparent volume (V) of the test piece. The mass (W) of the test piece is measured. The true volume (V1) of the test piece is measured using a dry automatic density meter. The value calculated by the following formulas 2 to 4 is the closed cell ratio. Each measurement is performed in an environment of a temperature of 23±5°C and a relative humidity of 40 to 70%. (Formula 2) Open cell rate (%): Oc = (V-V1) / V x 100 (Formula 3) Resin volume of polyurea foam: S=W / (V×D)×100 D is the density of the resin of the polyurea foam itself. (Formula 4) Closed bubble rate: Cc=100-Oc-S
[0057] 4-5.5% weight loss temperature The 5% weight loss temperature of the polyurea foam can be, for example, 120 to 320°C, and preferably 150 to 280°C. When the 5% weight loss temperature is within this range, a polyurea foam having the effects of the present invention can be obtained. The 5% weight loss temperature is measured using a simultaneous thermogravimetry / differential thermal analyzer (TG / DTA) to observe the weight loss behavior of the polyurea foam in the temperature range of 25 to 700°C, and the temperature at which the sample loses 5% by weight is measured. The measurement is performed at a temperature rise rate of 10°C / min under a dry air flow (flow rate: 250 mm / min).
[0058] 4-6. Measurement of ash content (600℃ and 700℃) The ash content of the polyurea foam when heated to 600°C can be, for example, 5 to 60% by weight, and is preferably 10% by weight or more. The ash content of the polyurea foam when heated to 700°C can be, for example, 3% by weight or more, and is preferably 5% by weight or more. When these values are within the above ranges, a polyurea foam having the effects of the present invention can be obtained. The ash content when heated to 600°C and 700°C is determined by observing the weight loss behavior of the polyurea foam in the temperature range of 25 to 600°C or 25 to 700°C using a simultaneous differential thermal / thermogravimetric analyzer (TG / DTA), measuring the residual weight of the polyurea foam at 600°C or 700°C, and dividing the weight by the initial weight of the polyurea foam to obtain the ash content (wt%) at 600°C or 700°C. The measurement is performed at a temperature rise rate of 10°C / min under a dry air flow (flow rate: 250 mm / min).
[0059] 4-7. Retention time (300℃ x 30 minutes, 500℃ x 30 minutes) The retained amount of the polyurea foam after 30 minutes of heat treatment at 300°C can be, for example, 30 to 95% by weight, preferably 55 to 95% by weight. The retained amount of the polyurea foam after 30 minutes of heat treatment at 500°C can be, for example, 15 to 65% by weight, preferably 25 to 65% by weight. When these values are within the above ranges, a polyurea foam having the effects of the present invention can be obtained. The retained amount when heated at 300°C and 500°C for 30 minutes is measured by using a simultaneous differential thermal / thermogravimetric analyzer (TG / DTA) to measure the weight of the polyurea foam remaining after heating to 300°C or 500°C and holding for another 30 minutes, and dividing the weight by the initial weight of the polyurea foam to obtain the retained weight (wt%). The measurement is performed by heating to a predetermined temperature at a heating rate of 10°C / min, holding the temperature, and under a dry air flow (flow rate: 250 mm / min).
[0060] 4-8.Compressive strength The compressive strength of the polyurea foam can be, for example, 300 to 800 kPa, and preferably 350 to 800 kPa. When the compressive strength is within this range, a polyurea foam having the effects of the present invention can be obtained. The compressive strength is measured by the method described in JIS K7220:2006 "Rigid foamed plastics - Determination of compression characteristics".
[0061] 4-9.Adhesive strength The adhesive strength of the polyurea foam to the wooden board can be, for example, 50 to 250 kPa, and preferably 70 to 250 kPa. When the adhesive strength is within this range, a polyurea foam having the effects of the present invention can be obtained. The adhesive strength is measured by the method described in JIS A9526:2015 "Sprayed rigid urethane foam for thermal insulation of buildings."
[0062] 4-10.Thermal conductivity The thermal conductivity of the polyurea foam is not particularly limited as long as it does not impair the effects of the present invention, but can be, for example, 0.015 to 0.040 W / (m·K), and preferably 0.015 to 0.026 W / (m·K). When the thermal conductivity is within this range, a polyurea foam having the effects of the present invention can be obtained. The thermal conductivity is measured by the method described in JIS A1412-1 "Method of measuring thermal resistance and thermal conductivity of thermal insulating materials - Part 1: Guarded hot plate method (GHP method)".
[0063] 4-11.Compressive elastic modulus The compressive elastic modulus of the polyurea foam can be, for example, 8 to 30 MPa, and preferably 10 to 30 MPa. When the compressive elastic modulus is within this range, a polyurea foam having the effects of the present invention can be obtained. The compressive elastic modulus is measured by the method described in JIS K7220:2006 "Rigid foamed plastics - Determination of compression characteristics".
[0064] 4-12. Moisture permeability coefficient (water vapor transmission rate) The moisture permeability coefficient of the polyurea foam can be, for example, 2.5 to 9.5 ng / (m2·s·Pa), and preferably 2.5 to 8.5 ng / (m2·s·Pa). When the moisture permeability coefficient is within this range, a polyurea foam having the effects of the present invention can be obtained. The permeability coefficient is measured by the method described in JIS K7225:2018 "Rigid plastic foam - Determination of water vapor permeability".
[0065] 4-13.Tensile strength The tensile strength of the polyurea foam can be, for example, 0.5 to 2.0 MPa, and preferably 0.6 to 2.0 MPa. When the tensile strength is within this range, a polyurea foam having the effects of the present invention can be obtained. The tensile strength is measured by the method described in JIS A9511:2017 "Foamed plastic heat-insulating material".
[0066] 4-14.Tensile elongation The tensile elongation of the polyurea foam can be, for example, 45 to 220%, and preferably 55 to 180%. When the tensile elongation is within this range, a polyurea foam having the effects of the present invention can be obtained. The tensile elongation is measured by preparing a test piece in accordance with the description in JIS A9511:2017 "Foamed Plastic Thermal Insulation Material" and drawing two parallel lines with a tensile direction distance of 50 mm. The test piece is subjected to a test at a tensile speed of 500 mm / min using a material testing machine, and the distance between the lines when the test piece breaks is measured. The tensile elongation is calculated as the measurement result (the distance between the lines at break) / 50 mm (the distance between the lines before the test)×100.
[0067] 4-15.Bending strength The flexural strength of the polyurea foam can be, for example, 0.02 to 0.15 MPa, and preferably 0.025 to 0.15 MPa. When the flexural strength is within this range, a polyurea foam having the effects of the present invention can be obtained. The flexural strength is measured by the method described in JIS K7221-2:2006 "Rigid foamed plastics - Bending test - Part 2: Determination of flexural properties".
[0068] 4-16.Charpy impact strength The Charpy impact strength of the polyurea foam can be, for example, 1.0 to 3.0 kg·cm / cm3, and preferably 1.2 to 3.0 kg·cm / cm3. When the Charpy impact strength is within this range, a polyurea foam having the effects of the present invention can be obtained. The Charpy impact strength is measured by the method described in JIS K7111-1:2012 "Plastics - Determination of Charpy impact properties - Part 1: Non-instrumented impact test".
[0069] 4-17.Water absorption rate The water absorption rate of the polyurea foam can be, for example, 0.012 to 0.050%, and preferably 0.015 to 0.045%. When the water absorption rate is within this range, a polyurea foam having the effects of the present invention can be obtained. The water absorption rate is calculated by dividing the amount of water absorption measured by the method B described in JIS A9511:2017 "Foamed plastic heat-insulating material" by the initial weight of the polyurea foam.
[0070] 4-18.Punching shear strength The punching shear strength of the polyurea foam can be, for example, 7 to 30 N / cm2, and preferably 8 to 25 N / cm2. When the punching shear strength is within this range, a polyurea foam having the effects of the present invention can be obtained. The punching shear strength is measured by the method described in JIS K7214:1985 "Shear test method by punching plastics".
[0071] 4-19.Durometer hardness (C hardness) The durometer hardness (C hardness) of the polyurea foam can be, for example, 25 to 65, and preferably 30 to 60. When the durometer hardness (C hardness) is within this range, a polyurea foam having the effects of the present invention can be obtained. The durometer hardness (C hardness) is measured by the method described in JIS K7215:1986 "Durometer hardness testing method for plastics".
[0072] 4-20.Specific Heat The specific heat of the polyurea foam can be, for example, 0.15 to 0.35 kJ / (kg·°C), and preferably 0.17 to 0.30 kJ / (kg·°C). When the specific heat is within this range, a polyurea foam having the effects of the present invention can be obtained. The specific heat is measured by a power compensation differential scanning calorimetry method described in JIS K7123:1987 "Method for measuring specific heat capacity of plastics."
[0073] 4-21. Cone calorimeter measurement (total heat generation) The total calorific value of the polyurea foam is measured in accordance with the ISO-5660 test method using a cone calorimeter under heating conditions with a radiant heat intensity of 50 kW / m2. The total calorific value after 10 minutes can be 15 MJ / m2 or less, preferably 10 MJ / m2 or less. The total calorific value after 20 minutes can be 15 MJ / m2 or less, preferably 10 MJ / m2 or less, more preferably 8 MJ / m2 or less. When the total calorific value of the polyurea foam is within this range, the polyurea foam has particularly excellent flame retardancy.
[0074] 5. Manufacturing method of polyurea foam The urea resin composition of the present invention is prepared by mixing the polyisocyanate compound (A), the polyamine compound (B), the catalyst, the blowing agent, the foam stabilizer, the red phosphorus, other flame retardants, and other additives in advance. A known method can be used as a method for mixing the urea resin composition. Specifically, the raw materials other than the polyisocyanate (A) are mixed in a container with a mixer (e.g., a mixer equipped with a propeller-type stirring blade) (e.g., stirring for 5 minutes at 2000 rpm using the stirrer) to prepare a composition for producing a polyurea foam. Subsequently, the polyisocyanate (A) and the composition for producing a polyurea foam are each cooled to a predetermined temperature (e.g., 10±1°C). Thereafter, the polyisocyanate (A) and the composition for producing a polyurea foam are mixed (e.g., stirring for 5 seconds at 2000 rpm using the stirrer) to obtain a urea resin composition. Furthermore, the urea resin composition is foamed and cured to obtain a polyurea foam. In addition, when using the spraying method, the composition for producing a polyurea foam, which is mixed with raw materials other than polyisocyanate in advance, and the polyisocyanate compound (A) are each supplied to a spray gun using a pump or the like (the nozzle of the spray gun is opened at this time), and the composition for producing a polyurea foam and the polyisocyanate compound (A) are mixed in a chamber in the spray gun, and sprayed onto a structure to obtain a polyurea foam. The composition for producing a polyurea foam, which is mixed with raw materials other than the polyisocyanate compound (A) in advance, and the polyisocyanate compound (A) can be handled as a two-liquid system liquid. In addition, a flame retardant, a foam stabilizer, a foaming agent, a dispersant, and other additives that do not react with the polyisocyanate compound (A) can also be mixed with the polyisocyanate compound (A) and handled as a system liquid.
[0075] The content of the polyamine compound (B) in the urea resin composition is 2.0% by mass or more, preferably 5.0% by mass or more, and more preferably 8.0% by mass or more, when the total amount of the urea resin composition is 100% by mass. The upper limit of the content of the polyamine compound (B) can be, for example, 40.0% by mass or less, preferably 30.0% by mass or less, and more preferably 20.0% by mass or less. From another perspective, the content of the polyamine compound (B) in the urea resin composition can be blended so that the isocyanate index of the urea resin composition is 200 to 600, and more preferably 200 to 500. Here, the isocyanate index refers to the ratio of the number of moles of all active hydrogens in the resin composition, which is the total raw material blend, to the number of moles of isocyanate groups in the polyisocyanate compound (A) multiplied by 100 (number of moles of NCO / number of moles of active hydrogen × 100). When the isocyanate index of the resin composition is within this range, a sufficient isocyanurate structure is formed, and the isocyanurate ratio can be made appropriate, so that the polyurea foam can have excellent flame retardancy. In addition, when the polyisocyanate compound (A) and the composition for producing a polyurea foam, which is a mixture of raw materials other than the polyisocyanate compound (A), are treated as a two-component system liquid, the content of the polyamine compound (B) in the composition for producing a polyurea foam is 2.0% by mass or more, preferably 5.0% by mass or more, and more preferably 8.0% by mass or more, when the sum of the composition for producing a polyurea foam and the polyisocyanate compound (A) is taken as 100% by mass. The upper limit of the content of the polyamine compound (B) can be, for example, 40.0% by mass or less, preferably 30.0% by mass or less, and more preferably 20.0% by mass or less. From another perspective, the content of the polyamine compound (B) in the composition for producing a polyurea foam can be blended so that the isocyanate index when the composition for producing a polyurea foam and the polyisocyanate compound (A) are mixed is 200 to 600, and more preferably 200 to 500.
[0076] The content of the polyisocyanate compound (A) in the urea resin composition can be 100 to 1000 parts by mass, assuming that the total content of the polyamine compound (B) in the urea resin composition is 100 parts by mass. When the polyurea foam-producing composition and the polyisocyanate compound (A) are handled as a two-component system liquid, the amount of the polyamine compound (B) in the polyurea foam-producing composition can be 100 to 1,000 parts by mass, assuming that the total content of the polyamine compound (B) in the polyurea foam-producing composition is 100 parts by mass.
[0077] The content of the foam stabilizer in the urea resin composition or the composition for producing a polyurea foam can be 0.1 to 20 parts by mass, relative to 100 parts by mass of the total content of the polyamine compound (B) in the urea resin composition or the composition for producing a polyurea foam. The content of the foam stabilizer in the polyurea foam can be 0.1 to 20% by mass, and preferably 0.5 to 15% by mass, relative to 100% by mass of the total mass of the polyurea foam.
[0078] The content of the flame retardant in the urea resin composition or the composition for producing a polyurea foam can be 10 to 200 parts by mass, preferably 30 to 150 parts by mass, and more preferably 50 to 100 parts by mass, when the total content of the polyamine compound (B) in the urea resin composition or the composition for producing a polyurea foam is taken as 100 parts by mass. When the content of the flame retardant is within this range, a polyurea foam having excellent flame retardancy can be obtained. In addition, the content of the flame retardant contained in the polyurea foam can be 1 to 60% by mass, and preferably 2 to 45% by mass, when the total mass of the polyurea foam is taken as 100% by mass.
[0079] The content of red phosphorus in the urea resin composition or the composition for producing a polyurea foam can be 100 parts by mass or less, preferably 5 to 40 parts by mass, and more preferably 25 to 40 parts by mass, when the total content of the polyamine compound (B) in the urea resin composition or the composition for producing a polyurea foam is taken as 100 parts by mass. The content of red phosphorus contained in the polyurea foam can be 0 to 30% by mass, preferably 1 to 30% by mass, and more preferably 2 to 25% by mass, when the total mass of the polyurea foam is taken as 100% by mass. When the content of red phosphorus is within this range, a polyurea foam with better flame retardancy can be obtained, and deterioration over time in a humid and hot environment can be suppressed. In particular, the ash content after thermal decomposition of the foam increases, and in the flame contact evaluation described below, a non-flammable carbonized layer is formed at the beginning of flame contact, thereby preventing combustion from progressing to the depth of the foam. The total content of the flame retardants selected from phosphoric acid esters, phosphate-containing flame retardants, bromine-containing flame retardants, boron-containing flame retardants, antimony-containing flame retardants, and metal hydroxides can be 10 to 200 parts by mass, assuming that the total content of the polyamine compound (B) in the urea resin composition is 100 parts by mass. The ratio (Fp / Ft) of the content of red phosphorus (Fp) in the urea resin composition to the total content (Ft) of the flame retardants selected from phosphoric acid esters, phosphate-containing flame retardants, bromine-containing flame retardants, boron-containing flame retardants, antimony-containing flame retardants, and metal hydroxides is not particularly limited, but can be, for example, 0.0 to 1.0, preferably 0.0 to 0.8, more preferably 0.09 to 0.73, and even more preferably 0.45 to 0.73. When the blending amount of these flame retardants is within the above range, a polyurea foam can be obtained that has excellent flame retardancy and shape retention during combustion and is capable of suppressing deterioration over time in a moist and hot environment.
[0080] The content of the trimerization catalyst in the urea resin composition or the composition for producing a polyurea foam can be 0.1 to 30 parts by mass, preferably 1 to 20 parts by mass, more preferably 5 to 20 parts by mass, and even more preferably 10 to 20 parts by mass, when the total content of the polyamine compound (B) in the resin composition or the composition for producing a polyurea foam is taken as 100 parts by mass. When the content of the trimerization catalyst is within this range, the isocyanuration is sufficient, and a polyurea foam having excellent flame retardancy and shape retention during combustion and capable of suppressing deterioration over time in a humid and hot environment can be obtained. In addition, the content of the trimerization catalyst contained in the polyurea foam can be 0.01 to 20% by mass, preferably 0.05 to 15% by mass, when the total mass of the polyurea foam is taken as 100% by mass.
[0081] The content of the foaming agent in the urea resin composition or the composition for producing a polyurea foam can be 1 to 60 parts by mass, preferably 5 to 50 parts by mass, when the total content of the polyamine compound (B) in the resin composition or the composition for producing a polyurea foam is taken as 100 parts by mass. When the content of the foaming agent is within this range, a polyurea foam can be obtained that has excellent flame retardancy and shape retention during combustion and can suppress deterioration over time in a humid and hot environment. In addition, the content of the foaming agent in the polyurea foam can be 1 to 40% by mass, preferably 3 to 30% by mass, when the total mass of the polyurea foam is taken as 100% by mass.
[0082] When a catalyst other than the trimerization catalyst (such as a resinification catalyst or a foaming catalyst) is blended, the content of the catalyst other than the trimerization catalyst can be 1 to 10 parts by mass, where the total content of the polyamine compound (B) in the urea resin composition or the composition for producing a polyurea foam is 100 parts by mass. A compound having both the functions of a resinification catalyst and a foaming catalyst is blended as a resinification catalyst. The content of the catalyst other than the trimerization catalyst contained in the polyurea foam can be 0 to 20% by mass, and preferably 0.5 to 15% by mass, where the total mass of the polyurea foam is 100% by mass.
[0083] 6. Applications of polyurea foam The polyurea foam of the present invention is used for architectural applications (walls, ceilings, roofs, floors, etc.), fittings (windows, shoji screens, sliding doors, sliding doors, transoms, etc.), ships and storage tanks for transporting oil and gas, vehicles (engines, batteries, ceilings, floors, door panels, etc.), aircraft, transport aircraft, cold storage bags for transporting medicines, freezers and refrigerators, plant facilities, and electrical appliances such as refrigerators, insulation materials, heat materials, and cold resistance mitigation materials for retaining walls, underground filling reinforcement materials during land subsidence prevention work and road construction, injection repair materials for civil engineering applications such as tunnels, bridges, and floating piers, structural filling materials for unnecessary basements, energy absorbing materials, waterproofing materials, water-stopping materials, buoyancy materials, etc. In addition, in buildings made of wood or reinforced concrete, etc., it can be used as a polyurea foam for spraying construction methods because it is easy to apply heat insulation. EXAMPLES
[0084] <<Preparation of resin composition>> <Raw materials> (Polyamine compound (B)) Ethacure 420 (manufactured by Albemarle, amine value: 562 mg KOH / G) Elasmer 250P (Kumiai Chemical Industry Co., Ltd., amine value: 254 mg KOH / g) ANCAMINE 2049 (Evonik, amine value: 484 mg KOH / g) Elasmer 1000P (Kumiai Chemical Industry Co., Ltd., amine value: 93 mg KOH / g) (Polyol Compound) Maximol RLK-505 (Kawasaki Chemical Industries, Ltd., hydroxyl value: 250 mg KOH / g) (Flame retardant) Tris(2-chloropropyl) phosphate (TMCPP, a chlorine-containing phosphate ester) Resorcinol bis(diphenyl)phosphate (PFR, phosphoric acid ester) ·Red phosphorus Ammonium polyphosphate (phosphate-containing flame retardant) Aluminum hypophosphite (a phosphinate-containing flame retardant) Sodium hypophosphite (a phosphinate-containing flame retardant) Decabromodiphenyl oxide (bromine-containing flame retardant) Zinc borate (a boron-containing flame retardant) Antimony trioxide (antimony-containing flame retardant) Aluminum hydroxide (metal hydroxide flame retardant) Expanded graphite DOWSIL TM-4 7081 (Dow Toray, acrylic modified silicone resin, silicone flame retardant) (Foam stabilizer) SF2937F (Toray Dow Corning silicone surfactant) Disparlon SEI-1501 (Kusumoto Chemicals, acrylic polymer, organic surfactant) (catalyst) Bismuth 2-ethylhexanoate (bismuth catalyst) ·Dibutyltin dimercaptide (tin catalyst) ·N,N-Dimethylaminoethanol (foam catalyst) Titanium tetra(2-ethylhexoside) (titanium catalyst) ·TEDA (triethylenediamine, amine catalyst) ·BDMAEE (Bis(dimethylaminoethyl) ether) 1,2-Dimethylimidazole PMDETA (Pentamethyldiethyltriamine) ·TOYOCAT-TRX (Tosoh Corporation, trimerization catalyst) · U-CAT 18X (San-Apro, quaternary ammonium salt, trimerization catalyst) · Diazabicycloundecene (trimerization catalyst) 1,3,5-Tris(dimethylaminopropyl)hexahydro-s-triazine (trimerization catalyst) Potassium octylate (trimerization catalyst) (foaming agent) Opteon 1100 (Mitsui Fluorochemors, HFO-1336mzZ, boiling point 33°C) Opteon 1150 (Mitsui Fluorochemors, boiling point 7°C) Cyclopentane (boiling point 49°C) Water (boiling point 100℃) (Polyisocyanate compound (A)) Millionate MR-200 (Tosoh Corporation, NCO%: 30.9%, crude MDI) Foamlite MI (BASF INOAC Polyurethanes, NCO%: 33.3%, monomeric MDI) Cosmonate TM-50 (Mitsui Chemicals SKC Polyurethanes, NCO%: 39.5%, TDI / MDI mixture) In-house manufactured urethane prepolymer (NCO%: 27.0%, isocyanate-terminated urethane prepolymer) The in-house urethane prepolymer was prepared in the following manner. A 5L polyethylene container equipped with a mechanical stirrer, an anchor-type stirring blade, and a nitrogen inlet tube was charged with a predetermined amount of crude MDI (Tosoh Corporation, Millionate MR-200), and the liquid temperature of the isocyanate (crude MDI) was set to 25°C. A predetermined amount of polypropylene glycol (Mitsui Chemicals SKC Polyurethanes, Actocol D2000, hydroxyl value: 55.1) was added as a polyol in stages so that the liquid temperature did not exceed 80°C. After the addition of polypropylene glycol was completely completed, the mixture was stirred at a stirring speed of 60 rpm for 2 hours to react the isocyanate and polyol, thereby obtaining an isocyanate-terminated prepolymer. The NCO group content of the obtained prepolymer was measured in accordance with JIS K1603-1 (A method), and it was confirmed that the predetermined NCO group content was obtained.
[0085] <Preparation of foam> (Preparation of mixtures and foams for evaluations other than adhesiveness evaluation) In a 500 mL polypropylene disposable cup, the polyamine compound, polyol compound, trimerization catalyst, flame retardant, blowing agent, foam stabilizer, and other additives were weighed out in the amounts shown in Tables 1 to 7 for each Example and Comparative Example, and used as the mixed liquid for each Example and Comparative Example. Each mixed liquid was stirred and mixed at 2000 rpm for 5 minutes using a stirrer equipped with a propeller-type stirring blade, to obtain a composition for producing a polyurea foam and a polyol mixture for each Example and Comparative Example. The resulting polyamine mixed liquid and the polyisocyanate whose amounts shown in Tables 1 to 7 were weighed out were placed in a 10°C cooling furnace, and each was cooled to 10±1°C. The polyamine mixed liquid and polyol mixed liquid of each Example and Comparative Example, and the polyisocyanate were stirred and mixed at 2000 rpm for 5 seconds using a stirrer equipped with a propeller-type stirring blade, to foam and harden, to obtain the foam of each Example and Comparative Example. In addition, in the adhesiveness evaluation, the polyamine mixture and polyol mixture of each Example and Comparative Example, and the polyisocyanate whose content was measured out in Tables 1 to 7 were each cooled individually to 10±1°C, mixed with a hand spray for spraying rigid urethane foam described below, and sprayed onto the target object to form a foam for adhesiveness evaluation.
[0086] <<Evaluation>> The following evaluations were carried out for the foams of each Example and Comparative Example. Each foam was left to stand for 24 hours after foaming in an environment of 23±5°C temperature and 50±20% relative humidity for use. The evaluations marked "after moist heat treatment" indicate that the foams of each Example and Comparative Example after aging were subjected to moist heat treatment for one month in an environment of 80°C and RH85%, and then measured as the measurement sample after moist heat treatment of each Example and Comparative Example. The measurement method was the same as that when "moist heat treatment" was not performed. <Measurement of isocyanurate ratio> The foams of each Example and Comparative Example were subjected to infrared absorption spectrum measurement using a Fourier transform infrared spectrometer (FT-IR, JASCO Corporation, Model FT / IR-4200). The measurement was performed by the ATR method using a diamond prism, and the measurement was performed 50 times. The isocyanurate ratio in the foam was calculated from Equation 1. The measurement was performed at three points in the rise direction of the foam, the top, the center, and the bottom, and the average value was calculated. The measurement results are shown in Tables 1 to 7. (Observed peak) P1: Peak area derived from the isocyanurate structure contained in the absorption spectrum of the foam obtained by infrared spectroscopy (observation range: 1380-1430 cm-1) P2: Peak area derived from C=O of the urea structure contained in the absorption spectrum of polyurea foam obtained by infrared spectroscopy (observation range: 1550-1640 cm-1) P3: Peak area derived from C=O of urethane structure and isocyanurate structure contained in the absorption spectrum of foam obtained by infrared spectroscopy (observation range: 1680-1730 cm-1) P4: Peak area derived from the polyurea structure and NH contained in the urea structure in the absorption spectrum of the foam obtained by infrared spectroscopy (observation range: 1470 to 1550 cm-1) (Formula 1) Isocyanurate ratio = P1 / (P1+P2+P3+P4) x 100
[0087] <density> The apparent density of the foams of each of the Examples and Comparative Examples was measured by the method described in JIS K7222:2005 "Foamed plastics and rubber - Determination of apparent density." The results are shown in Tables 8 to 14.
[0088] <Average cell (air bubble) diameter and cell shape> The composition for producing a polyurea foam and the polyol mixture of each Example and Comparative Example were mixed with a polyisocyanate by the above method, and foamed and cured in a mold to obtain a foam of each Example and Comparative Example. A test piece of 50 mm in length x 50 mm in width x 20 mm in thickness was cut out from each obtained foam, and the bubbles in the CD and MD planes were observed using a digital microscope (Keyence VHX-800) to confirm their shapes. At that time, 10 bubbles were randomly selected on the CD plane, and the difference (DR = R1 - R2) between the longest diameter (R1) of each bubble in the CD plane and the diameter in the direction perpendicular to the longest diameter (R2) was obtained, and when the average DR of all selected bubbles exceeded 5 mm, it was judged to be an elliptical shape. In addition, a shape of 0 mm or more and 5 mm or less was judged to be a circular shape. In addition, 10 bubbles in each of the CD and MD were randomly selected, and the length of their major axis was measured. The average of these was taken as the average cell diameter in the CD and the average cell diameter in the CD. The ratio of the average cell diameter in the MD to the average cell diameter in the CD (average cell diameter in the MD / average cell diameter in the CD) was also calculated. The results are shown in Tables 8 to 14.
[0089] <Closed bubble rate> The closed cell ratio of the foams of each Example and Comparative Example was measured by the following method. The foams of each Example and Comparative Example were processed into test pieces of 30 mm length x 30 mm width x 20 mm thickness, and the length of each side was accurately measured to calculate the apparent volume (V) of the test pieces. The mass (W) of the test pieces was measured. The true volume (V1) of the test pieces was measured using a dry automatic density meter (Shimadzu Corporation, Micromeritics Accupic II 1340). Using these values, the values calculated from the following formulas 2 to 4 were taken as the closed cell ratio. Each measurement was performed in an environment of 23±5°C temperature and 40 to 70% relative humidity. (Formula 2) Open cell rate (%): Oc = (V-V1) / V x 100 (Formula 3) Resin volume of polyurea foam: S=W / (V×D)×100 D is the density of the resin of the polyurea foam itself. (Formula 4) Closed bubble rate: Cc=100-Oc-S The results are shown in Tables 8 to 14.
[0090] <5% weight loss temperature> Approximately 10 mg of each foam from each Example and Comparative Example was sampled, and the temperature at which the sample weight decreased by 5% by weight was measured using a thermogravimetric analyzer (abbreviated as TGA) when the temperature was raised from 25 to 600°C. The measurement was performed under conditions of a temperature rise rate of 10°C / min and an air flow of 200 ml / min. The results are shown in Tables 8 to 14. Measurements were also performed on the foams after the moist heat treatment, and the results are shown in Tables 15 to 21.
[0091] <Measurement of ash content (600℃, 700℃)> 3 to 5 mg was taken from the center of the foam of each Example and Comparative Example, and the sample was filled in an aluminum pan (for measurement at 600°C) or a platinum pan (for measurement at 700°C). The weight loss behavior of the sample was observed in the temperature range of 25 to 600°C or 25 to 700°C using a TG / DTA measuring device (TG / DTA7200 manufactured by SII Co., Ltd.), and the ash content (%) of each foam was calculated from the remaining weight of the sample at 600°C or 700°C. The measurement was performed at a temperature rise rate of 10°C / min under a dry air flow (flow rate: 250 mm / min). The results are shown in Tables 8 to 14. Measurements were also performed on the foam after the moist heat treatment, and the results are shown in Tables 15 to 21.
[0092] <Residual retention time (300℃ x 30 minutes, 500℃ x 30 minutes)> The foams of each Example and Comparative Example were heated to 300°C or 500°C using a simultaneous thermogravimetry and differential thermal analyzer (TG / DTA) and then held for 30 minutes, after which the remaining weight of each foam was measured and divided by the initial weight of the polyurea foam to obtain the retained weight (wt%). The measurement was performed at a heating rate of 10°C / min, at a prescribed temperature, and held at that temperature. Evaluation was also performed under a dry air flow (flow rate: 250 mm / min). The results are shown in Tables 8 to 14. Measurements were also performed on the foams after the moist heat treatment, and the results are shown in Tables 15 to 21.
[0093] <Compressive strength> The compressive strength of the foams of each Example and Comparative Example was measured by the method described in JIS K7220:2006 "Rigid foamed plastics - Determination of compressive properties". The results are shown in Tables 8 to 14. In addition, the foams after the moist heat treatment were also measured, and the results are shown in Tables 15 to 21.
[0094] <Adhesive strength> The adhesive strength of the foams of each Example and Comparative Example was measured by the method described in JIS A9526:2015 "Spray-on rigid urethane foam for thermal insulation of buildings." The results are shown in Tables 8 to 14. The foams after the moist heat treatment were also measured, and the results are shown in Tables 15 to 21.
[0095] <Measurement of thermal conductivity> The thermal conductivity of the foams of each Example and Comparative Example was measured according to JIS A1412-1:2016 "Method of measurement of thermal resistance and thermal conductivity of thermal insulation materials - Part 1: Guarded hot plate method (GHP method)". The results are shown in Tables 8 to 14. In addition, the foams after the moist heat treatment were also measured, and the results are shown in Tables 15 to 21.
[0096] <Compressive elastic modulus> The compressive elastic modulus of the foams of each Example and Comparative Example was measured by the method described in JIS K7220:2006 "Rigid foamed plastics - Determination of compression properties." The results are shown in Tables 8 to 14. Measurements were also performed on the foams after moist heat treatment, and the results are shown in Tables 15 to 21.
[0097] <Moisture permeability coefficient (water vapor transmission rate)> The moisture permeability coefficient of the foams of each of the Examples and Comparative Examples was measured by the method described in JIS K7225:2018 "Rigid plastic foam - Determination of water vapor permeability." The results are shown in Tables 8 to 14.
[0098] <Tensile strength> The tensile strength of the foams of each of the Examples and Comparative Examples was measured by the method described in JIS A9511:2017 "Foamed plastic heat-insulating material." The results are shown in Tables 8 to 14.
[0099] <Tensile elongation> The tensile elongation of the foams of each Example and Comparative Example was measured by the following method. Test pieces were prepared according to the description in JIS A9511:2017 "Foamed Plastic Thermal Insulation Material", and two parallel lines with a tensile direction distance of 50 mm were drawn. The test pieces were tested at a tensile speed of 500 mm / min using a material testing machine, and the distance between the lines when the test pieces broke was measured. The tensile elongation was calculated as the measurement result (the distance between the lines at break) / 50 mm (the distance between the lines before the test)×100, and the results are shown in Tables 8 to 14.
[0100] <Bending strength> The flexural strength of the foams of each of the Examples and Comparative Examples was measured by the method described in JIS K7221-2:2006 “Rigid foamed plastics - Bending test - Part 2: Determination of flexural properties.” The results are shown in Tables 8 to 14.
[0101] <Charpy impact strength> The Charpy impact strength of the foams of each of the Examples and Comparative Examples was measured by the method described in JIS K7111-1:2012 "Plastics - Determination of Charpy impact properties - Part 1: Non-instrumented impact test." The results are shown in Tables 8 to 14.
[0102] <Water absorption rate> The water absorption rate of the foams of each Example and Comparative Example was calculated by dividing the amount of water absorption measured by Method B described in JIS A9511:2017 "Foamed Plastic Thermal Insulation Material" by the initial weight of each foam. The results are shown in Tables 8 to 14.
[0103] <Punching shear strength> The punching shear strength of the foams of each of the Examples and Comparative Examples was measured by the method described in JIS K7214:1985 "Shear test method by punching plastics." The results are shown in Tables 8 to 14.
[0104] <Durometer hardness (C hardness)> The durometer hardness (C hardness) of the foams of each of the Examples and Comparative Examples was measured by the method described in JIS K7215:1986 "Durometer hardness testing method for plastics." The results are shown in Tables 8 to 14.
[0105] <Specific heat> The specific heat of the foams of each of the Examples and Comparative Examples was measured by a power compensation differential scanning calorimetry method described in JIS K7123:1987 "Method for measuring specific heat capacity of plastics." The results are shown in Tables 8 to 14.
[0106] <Dimensional change before and after wet heat treatment> The foams of each Example and Comparative Example were subjected to a moist heat treatment for one month under an environment of 80°C and RH 85%, and the dimensional change rate before and after the moist heat treatment was measured. The measurement sample of the foam was 100 mm long x 100 mm wide x 20 mm thick, and the dimensions of the measurement sample were measured using a vernier caliper. The results are shown in 15 to 21.
[0107] <Volume change rate (600℃)> A sample measuring 5 cm in length x 5 cm in width x 5 cm in thickness was cut out from the center of the foam of each Example and Comparative Example, and left to stand for 5 minutes in an electric furnace heated to 600°C, and the volume change rate was measured. The volume before heating was taken as 100%, and the volume after heating was measured. The volume after heating was subtracted from the volume before heating, and the result was divided by the volume before heating and multiplied by 100 to obtain the volume change rate. If the sample expanded, a positive value is shown, and if the sample contracted, a negative value is shown. The results are shown in Tables 15 to 21.
[0108] <Adhesiveness> The polyamine mixture and polyol mixture of each Example and Comparative Example, and the polyisocyanate whose content is shown in Tables 1 to 7 were individually cooled to 10±1°C, and then mixed and sprayed onto the surface of a wooden board whose surface temperature was set to 15°C using a hand sprayer for spraying rigid urethane foam (manufactured by ADY Co., Ltd.), and foamed on the surface of the wooden board. After that, the boards were cured for 24 hours, and those that had no peeling or lifting at the adhesive interface between the wooden board and the foam were scored as 1, and those that had peeling or lifting were scored as 0. The results are shown in Tables 15 to 21.
[0109] <Flame contact test> From the foams of each Example and Comparative Example 24 hours after foaming, a rectangular parallelepiped sample with a length of 10 cm, a width of 10 cm, and a thickness of 5 cm was cut out. Each obtained sample was placed on a wire mesh with a length of 10 cm, a width of 10 cm, and a thickness of 1 mm, and a flame was applied to the surface of the sample for 3 minutes using a gas burner. Methane gas with a purity of 99.5% or more was used as the combustion gas, and the combustion gas was supplied at 0.2 MPa to produce a pale blue flame. The height of the flame was set to 5 cm, and the distance between the flame and the sample surface was set to 1 cm. After exposure to flame, the sample was cut in half, and the presence or absence of cracks on the cross section was visually observed. In addition, the maximum distance of the blackened carbonized part on the cross section (the length of the carbonized part from the side surface of the cross section) was measured as the depth of the carbonized layer. The results are shown in Tables 1 to 3. In addition, the evaluation was judged according to the following evaluation criteria, and the results are shown in Tables 15 to 21. In addition, "not measurable" in the table indicates that the measurement was not possible because the flame penetrated the sample when it was exposed to flame.
[0110] <Total heat generation (50kW x 10min, 20min) measurement> A sample having a length of 10 cm, a width of 10 cm, and a thickness of 5 cm was cut out from the center of the foam of each Example and Comparative Example, and a cone calorimeter total heat generation test was carried out on the foam in accordance with the standard ISO-5660 (Building Standards Act No. 2) to measure the total heat generation and maximum heat generation rate of the sample. The measurement was performed with a radiant heat amount of 50 kW / m2 and a measurement time of 10 minutes and 20 minutes. The results are shown in Tables 15 to 21. Note that the word "measurable" in the tables indicates that the expanded sample came into contact with the tip of the spark plug of the cone calorimeter during the test, causing no spark to be generated, and normal measurement was not possible.
[0111] For each of the foams of the Examples and Comparative Examples, a UL94 flame retardancy test was conducted in accordance with the 5VA standard, and the burning distance, burning time, whether drip / cotton ignition occurred, whether flame penetration occurred, and the size of the penetration hole were measured.
[0112] <Evaluation using actual equipment (spray)> In a pail container, the polyamine compound, the flame retardant, the catalyst, the foam stabilizer, and the foaming agent were weighed according to the formulation of Examples 1, 18, and 92 described in Tables 1, 2, and 7, and stirred for 5 minutes with a power mixer (manufactured by Ryobi, model number PM-1511) at room temperature to prepare an amine mixed liquid (system liquid). A spray gun (manufactured by Graco, Fusion Gun) was attached to the device body (manufactured by Graco, HR-V), and the temperature of the pump and hose was set to 40°C. The pump was operated, and the amine mixed liquid (system liquid) and the polyisocyanate that had been sufficiently stirred separately were adjusted so that the difference in the liquid pressure of the liquid sent was within 2.0 MPa. The nozzle of the spray gun was opened, and the amine mixed liquid (system liquid) and the isocyanate were mixed in the chamber inside the gun, and sprayed onto the body to prepare the foam of Examples 1, 18, and 92, and the same evaluation was performed as in the above-mentioned method without using a spray. The foams having the same formulation as those in Examples 1, 18, and 92 gave evaluation results similar to those of Examples 1, 18, and 92, respectively.
[0113] [Table 1]
[0114]
Table 2
[0115]
Table 3
[0116]
Table 4
[0117]
Table 5
[0118]
Table 6
[0119]
Table 7
[0120]
Table 8
[0121]
Table 9
[0122]
Table 10
[0123]
Table 11
[0124]
Table 12
[0125]
Table 13
[0126]
Table 14
[0127]
Table 15
[0128]
Table 16
[0129]
Table 17
[0130]
Table 18
[0131]
Table 19
[0132]
Table 20
[0133]
Table 21
Claims
1. A urea resin composition comprising a polyisocyanate compound (A), a polyamine compound (B), a trimerization catalyst, a foaming agent, and a foam stabilizer, A urea resin composition which does not contain a polyol compound or has a polyol compound content of 1 / 5 or less in terms of mass ratio to the content of the polyamine compound (B).
2. A polyurea foam obtained by foaming and curing the urea resin composition according to claim 1.
3. Production of polyurea foam containing polyamine compound (B), trimerization catalyst, blowing agent and foam stabilizer A composition for use, comprising: A composition for producing a polyurea foam, which does not contain a polyol compound, or the content of the polyol compound is 1 / 5 or less in terms of mass ratio relative to the content of the polyamine compound (B).
4. The composition comprises a polyisocyanate compound (A), a polyamine compound (B), a trimerization catalyst, a foaming agent, a foam stabilizer, and a flame retardant, The polyamine compound (B) is at least one selected from the group consisting of 4,4'-diamino-3,3'-dichlorodiphenylmethane, trimethylene-bis(4-aminobenzoate), 4,4'-diamino-3,3'-diethyl-5,5'-dimethyldiphenylmethane, polytetramethylene oxide-di-p-aminobenzoate, 2,2',6,6'-tetraethyl-4,4'-methylenedianiline, 4,4'-methylenebis(2-isopropyl-6-methylaniline), 4,4'-methylenebis(2,6-diisopropylaniline), 4,4'-methylenebis(3-chloro-2,6-diethylaniline), 3,5-diethyltoluene-2,4-diamine, and dimethylthiotoluenediamine. A urea resin composition.
Citation Information
Patent Citations
Production of rigid isocyanurate spray foam
JP1999292949A
Flame resistant heat insulation composition
JP2015078357A
Polyol composition for spray coating, foamable polyurethane premix composition, and foamable polyurethane composition
JP2018100404A
Foamable composition for flame-retardant polyurethane foam
JP2020007386A
Hollow light transmission plate main body and hollow light transmission plate using the same
JP1995005326A